The Public Perceptions and Preferences on Brahu Temple as a Cultural Heritage (Bejijong Village, Trowulan Mojokerto) - Rukmana, Siti Nuurlaily; Sucipto, Sucipto; Eliyanto, Aprillia Putri; Widyastuty, Anak Agung Sagung Alit (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2023)
The Mojokerto Regency government program is nothing compared to the number of tourists who visit the Brahu temple attraction because there has been a decrease in the number of visitors within the last five years, from 2017-2021. Based on data from the East Java Cultural Heritage Protection and Preservation Agency (BPCB), the number of visitors who visited Brahu Temple was 62,854 in 2017, and there were 1068 people in 2021. The study aimed to determine public perceptions and preferences of Brahu Temple as a Cultural Heritage in Bejijong Village, Trowulan District, Mojokerto. The data collection methods used were observation and a questionnaire. The descriptive and qualitative research methodology uses IPA analysis techniques (Importance Performance Analysis). The study results show that the main priority for visiting a Cultural Heritage site at Brahu Temple is the temple's culture and values. It means visitors who visit the temple have particular goals or interests because they want to know and learn things. It includes temple culture in the form of aesthetics, originality, and the age of the temple, as well as the values contained in a Cultural Heritage at Brahu Temple such as Educational, Religious, Cultural, and Historical Values. In this case, the public perception and preference of Brahu Temple as a Cultural Heritage from the IPA analysis with 115 respondents found that the results